
Алгебра • Система Уравнений |
10.06.16 09:38 |
Я так попытался:
[math](x+y)(x^2-xy+y^2)=19[/math] [math](x+y)(xy+8)=2[/math] или [math]-(x+y)\big [xy+8-(x^2+y^2+8) \big ]=19[/math] [math](x+y)(xy+8)=2[/math] Делаем замены: [math]p=x+y \, ; \quad q=xy+8 \, ; \quad A=x^2+y^2+8[/math] Тогда [math]-p(q-A)=19[/math] [math]pq=2[/math] Если [math]A\ne 0[/math] то [math]p=\frac{21}{A}\, ; \quad q=\frac{2A}{21}[/math] или [math]A=21\, ; \quad p=1\, ; \quad q=2[/math] Получается система [math]x^2+y^2+8=21[/math] [math]x+y=1[/math] [math]xy+8=2[/math] Последние две строки дают: [math]x=-2 \, ; \quad y=3[/math] и [math]x=3 \, ; \quad y=-2[/math] К счастью, эти решения не противоречат и первой строке. |